Efficient spin accumulation carried by slow relaxons in chiral tellurium - Evgenii Barts; Karma Tenzin; Jagoda Sławińska (Nature Communications)
Abstract Efficient conversion between charge currents and spin signals is crucial for realizing magnet-free spintronic devices. However, the strong spin-orbit coupling that enhances this conversion also causes rapid spin dissipation, making spin signals difficult to control. Although modern materials science offers novel systems with diverse spin configurations of conduction electrons, understanding their fundamental limitations requires insights into the mechanisms behind the creation and relaxation of spin populations. In this study, we demonstrate that parallel spin-momentum entanglement at the Fermi surface of chiral tellurium crystals gives rise to slow collective relaxation modes, termed relaxons. These relaxons dominate the electrically generated spin and orbital angular momentum accumulation in tellurium, achieving an extraordinary 50% conversion efficiency, and are responsible for a long lifetime of the spin population. We show that the slow relaxons carrying spin density closely resemble the persistent helical spin states observed in GaAs semiconductor quantum wells. This similarity suggests that slow relaxons are a general phenomenon, potentially present in other chiral materials with strong spin-momentum locking, and could be used to generate and transmit spin signals with low heat losses in future electronics.